Potential Role of Cytokines and Vitamin D in Pathophysiology of Autism Spectrum Disorder (Texas Journal of Medical Science, 2022)
Autism spectrum disorder is a neurodevelopmental condition with a wide range of symptoms. An early stage begins before the age of 3. Autistic people have trouble socializing, communicating verbally and nonverbally, as well as having stereotypical interests and behaviors. Due to the increasing frequency of autism in children and the lack of effective treatments, it is one of the most challenging conditions to treat in psychology. Autism has a perplexing etiology. Immune regulation of neuronal proliferation, synapse formation, and plasticity are all enhanced by the chemosensory immune system. Immune responses in autistic people are aberrant, according to hundreds of studies conducted over the past four decades. Vitamin D deficiency, as well as cytokine profile and signaling abnormalities, have become increasingly prevalent in recent years and have been the focus of continuing research in the field of autism spectrum disorder. Numerous studies indicate that vitamin D plays a significant role as a neuroactive steroid that can influence neuronal development, axonal connections, and brain structure and function. In addition, vitamin D insufficiency during pregnancy is associated with a number of negative effects on the fetus. Immune abnormalities have previously been identified, and the role of cytokines in these abnormalities is highlighted in this review, which aims to determine whether cytokines are useful as potential biomarkers that may participate in the development of disease. The purpose of this review is to outline the function of the immune system and to examine the relationship between the immune biomarkers, cytokines with as emphasis on the role of vitamin D as an immune regulator.